2020
DOI: 10.31234/osf.io/7j8pb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parent-Child Conversations of Germ and Cold Weather Theories of the Common Cold in Two Cultures

Abstract: This study examines how children learn information about the causes of illness (such as germs or cold weather) through conversations with their parents in two cultures. Mexican (Study 1, N = 35) and European-American (Study 2, N = 31) mothers and their children (ages 4 to 6) read picture books in which one of the characters either got sick or did not get sick with the common cold. Mexican dyads discussed health and illness in terms of maintaining a balance in the body. European-American families relied on germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Children's beliefs about the reasons underlying health and illness can also vary in different sociocultural contexts (e.g., Gelman & Raman, 2004). One recent study by Hernandez et al (2020) examines parent-child conversations about the common cold and whether it is caused by virus or cold weather in two cultures: Mexican and European-American. The cold weather theory is an intuitive belief that people catch a common cold by just staying outside in the cold.…”
Section: Children's Knowledge Of Health and Illnessmentioning
confidence: 99%
“…Children's beliefs about the reasons underlying health and illness can also vary in different sociocultural contexts (e.g., Gelman & Raman, 2004). One recent study by Hernandez et al (2020) examines parent-child conversations about the common cold and whether it is caused by virus or cold weather in two cultures: Mexican and European-American. The cold weather theory is an intuitive belief that people catch a common cold by just staying outside in the cold.…”
Section: Children's Knowledge Of Health and Illnessmentioning
confidence: 99%
“…Rather than blending cold weather and germ theories in their explanations, however, cold weather theory was reserved for masuk angin alone, a form of “target-dependent” reasoning 2 ( Legare and Shtulman, 2018 ). Even for colds—which children and lay adults in other parts of the world often explain at least in part with cold conditions ( Helman, 1978 ; Baer et al, 1999 ; Sigelman, 2012 ; Hernandez et al, 2020 )—Indonesians seldom mentioned cold as a cause. Thus, masuk angin appears to have fully appropriated the cold weather theory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, young children, with relatively little familiarity with germ theory, may be more likely to provide intuitive/folknatural explanations for the different illnesses. However, it is possible that cold weather theory will cognitively coexist in the minds of older children and adults, rather than being replaced outright by scientific ideas ( Shtulman and Valcarcel, 2012 ; Legare and Shtulman, 2018 ; Kelemen, 2019 ; Hernandez et al, 2020 ). If so, will Indonesians incorporate cold and germ theories into a single explanation, or will they use different explanations for different illnesses?…”
Section: Introductionmentioning
confidence: 99%
“…One difference between our findings and prior work on parent-child conversations about illness is that in our sample we found that many of the questions were not about illness. In prior work, the conversations centered on health and illness with families rarely discussing other aspects such as changes to life style [10]. Although lifestyle changes are not unique to a pandemic (e.g., parents could talk about how children have to stay at home when they get a cold), they are probably more salient given the overall disruption to daily routines.…”
Section: Plos Onementioning
confidence: 99%